AWARENESS OF VIRAL MARKETING TOWARDS ENTREPRENEURS IN KELANTAN: AN APPLICATION OF TPB THEORY - Siti Maziah Binti Ab Rahman; Nur Hazelen Mat Rusok; Adeeba Najihah Binti Mohd Zaki (International Journal of Accounting, Finance and Business, 2024)
This study aims to investigate the awareness of the use of viral marketing among entrepreneurs in the State of Kelantan, by using the Theory of Planned Behavior (TPB) as a conceptual framework. The conclusion of this study is expected to provide a better understanding of the factors that influence the awareness and use of viral marketing among Kelantan entrepreneurs. The implications of these findings can guide stakeholders, including entrepreneurs, marketers, and policymakers, to develop more effective and contextual marketing strategies in the face of increasingly dynamic and digital market demands. By TPB approach, this paper is expected to provide a more holistic understanding of attitudes, norms, and controls that influence entrepreneurs' awareness of viral marketing in the State of Kelantan.